Burden and Associated Genotype Patterns of High-Risk Human Papilloma Virus Infection and Cervical Cytology Abnormalities among Women in Central India - Shipra Gupta; Shashank Purwar; Priyal Gupta; Ajay Halder; Ayush Gupta; K. Pushpalatha; Julie Hansa John (Hindawi Limited, 2022)
Background. The epidemiology of human papilloma virus (HPV) infection and the pattern of HPV genotype distribution are much-needed parameters to assess the risk of cervical cancer among females. However, due to less availability of data on HPV burden and its genotypes from various geographical regions in India makes cervical cancer screening modalities and vaccination strategies difficult to implement. Objective. The present study was conducted to identify the various genotypes particularly high-risk HPV types in premalignant or malignant cervical lesions. Methods. The study was a hospital-based cross-sectional study wherein 295 symptomatic women were screened by Pap smear and multiplex real-time PCR was performed for HPV genotypes identification in women with abnormal cervical cytology. Results. Out of 295 women, 237 (80.3%), 45 (15.3%), and 13 (4.4%) women had normal Pap smear, squamous cell carcinoma and precancerous cytology, respectively. Among these 58 women having abnormal cervical cytology, HPV was detected in 48 (81.0%) participants. Most common HPV genotypes in our study were HPV 16 (n=29; 60.4%) followed by mixed infections; i.e., more than one type of HPV was detected (n=10, 20.8%). HPV 18 was detected only in 6.25%, whereas other high-risk HPV genotypes were found to be 12.5%. Conclusion. HPV positivity was >80% in women having abnormal Pap smear. The prevalence of HPV 18 was found to be much less in Central India, compared to other parts of country. HPV 16 was the most common genotype followed by mixed HPV genotype infections. It is evident from our study that symptomatic women even if having normal Pap smear should be screened for HPV and followed up with periodic Pap smears for detecting any change in cervical cytology, thus preventing cervical cancer in women.